Software cost estimation and sizing methods : issues, and guidelines - Pfleeger, Shari Lawrence; Wu, Felicia; Lewis, Rosalind; Rand eBooks (Santa Monica, CA : RAND, 2005)
Accurate estimates of the software cost are a critical part of effective program management, particularly for large, complex systems. Predicting the cost of software has evolved, but the practice of cost prediction is far from perfect. Military and commercial programs alike are replete with examples of software cost estimates that differ significantly from the actual costs at completion. Software Cost Estimation and Sizing Methods: Issues and Guidelines recommends an approach to improving the utility and accuracy of software cost estimates by exposing uncertainty (in understanding the project) and reducing the risks associated with developing the estimates. The approach focuses on characteristics of the estimation process (such as which methods and models are most appropriate for a given situation) and the nature of the data used (such as software size). It describes risks in each of these factors in terms of symptoms and warning signs, and mitigation strategies for each. The techniques described in this report are based on a literature review and on analysis of software estimation and risk, in addition to general lessons and guidance adapted from selected programs. This report should be of particular interest to those organizations or agencies that use software estimates in the planning, budgeting, developing, or purchasing of software-intensive systems. It should also be of value to those involved in research and analysis of estimation models and techniques.
"RAND Project Air Force."
Includes bibliographical references (p. 93-97).
Also available on the internet via WWW in PDF format.
Keywords: United States. -- Air Force -- Procurement -- Mathematical models; Computer software -- Costs -- Estimates; Computer software -- Costs -- United States -- Forecasting; Computer software -- Development -- Management; Electronic books